2017
DOI: 10.1371/journal.pone.0167436
|View full text |Cite
|
Sign up to set email alerts
|

As Far as the Eye Can See: Relationship between Psychopathic Traits and Pupil Response to Affective Stimuli

Abstract: Psychopathic individuals show a range of affective processing deficits, typically associated with the interpersonal/affective component of psychopathy. However, previous research has been inconsistent as to whether psychopathy, within both offender and community populations, is associated with deficient autonomic responses to the simple presentation of affective stimuli. Changes in pupil diameter occur in response to emotionally arousing stimuli and can be used as an objective indicator of physiological reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 155 publications
4
42
3
Order By: Relevance
“…These areas were manually defined for each visual stimulus image, in accordance with previous studies (11,12,15,59). The averaged pupil diameter variation was also extracted, as in previous studies (18,60,61). The results of all the eye-tracking measures represent the averaged behavior of both eyes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These areas were manually defined for each visual stimulus image, in accordance with previous studies (11,12,15,59). The averaged pupil diameter variation was also extracted, as in previous studies (18,60,61). The results of all the eye-tracking measures represent the averaged behavior of both eyes.…”
Section: Discussionmentioning
confidence: 99%
“…First, those images or baselines that presented a ratio of missing data >50% in either eye were discarded (23,60,62,63). Second, the first 2 s of the stimuli were also discarded to remove the initial pupil contraction (60). Third, the non-physiological variations in pupil size, identified as those changes occurring at a faster rate than 5 mm/s, were removed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as presented in Figure a, we used a gray image without color to reduce the effect of screen luminescence over pupil size (Kohn & Clynes, ), and a scramble filter was initially applied to each question to hide its meaning, as in Ho and Lu () study of image context. To ensure that the appearance of the interviewer—an attractive 37‐year‐old woman—did not act as a stimulus for any subjects and affect their pupil size (Burley et al, ), the interviewer used a microphone outside the view of the subjects.…”
Section: Methodsmentioning
confidence: 99%
“…The exciting stimulus of a pleasant image can also affect the pupil size of subjects (Burley, Gray, & Snowden, ). Previous studies have reached the conclusion that explicit stimuli, that is, a woman dressed in a bikini, has a higher impact in terms of pupil size change, compared with nonexplicit arousal stimuli, that is, a fully dressed person (Watts, Holmes, Savin‐Williams, & Rieger, ).…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that psychopathy is associated with reduced attention to the eyes of affective faces. Another recent study investigated the relationship between pupil dilation and triarchic psychopathy and found that psychopathic traits were unrelated to emotion‐modulated pupil dilation (Burley, Gray, & Snowden, ). Together, these studies are part of a growing body of literature suggesting that psychopathy is not universally associated with facial affect recognition deficits.…”
Section: Introductionmentioning
confidence: 99%